Antistatic UV viscosity-reducing film and preparation method thereof
By synthesizing polyurethane A and polyurethane B, and adding conductive fillers and a crosslinking composition, an anti-static UV mucosa is prepared, which solves the problem that the UV mucosa lacks tensile resistance and anti-static ability when protecting wafers in the prior art. , achieving high adhesion and easy peeling effect.
Patent Information
- Application Number
- CN202411604702.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing UV mucosa lacks tensile resistance, antistatic ability and appropriate adhesion when protecting the wafer surface, resulting in the wafer being easily displaced or dropped during use, and at the same time, the viscosity is too high during disassembly and difficult to peel off.
Using a preparation method of antistatic UV mucosa, polyurethane A and polyurethane B are synthesized, and conductive fillers and a crosslinking composition are added to form a multi-branched structure adhesive, coated on the substrate and pasted on the release type. membrane, forming a UV mucosa. This method utilizes the multi-branched structure of polyurethane A and the low molecular weight characteristics of polyurethane B, and combines conductive fillers and modification additives to improve mechanical strength, antistatic properties and processing properties.
The UV mucosa reduces the film with high adhesion, antistatic properties and good peeling properties on the wafer surface. The adhesive force decreases after UV irradiation, is easy to peel, and ensures the protection and processing convenience of the wafer.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives, and specifically discloses an antistatic UV viscosity-reducing film and a preparation method thereof. Background Art
[0002] UV anti-viscosity film is a special adhesive film that has high bonding strength under normal conditions and quickly reduces viscosity after ultraviolet light. It is mostly used to protect the surface of wafers and can be easily removed after the protection process is completed without affecting the material itself.
[0003] Since wafers are thin and brittle, the performance of UV adhesive is increasingly required: it needs to have good tensile strength, good antistatic ability, and sufficient adhesion to protect the wafer surface and ensure that the wafer does not move or fall during use; it also needs to have a low enough viscosity after UV adhesive removal to facilitate the disassembly and peeling of the wafer. Therefore, it is of great significance to study a UV adhesive film with the above properties. Summary of the invention
[0004] The object of the present invention is to provide an antistatic UV anti-viscosity film and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing an antistatic UV anti-viscosity film: comprising the following steps: S1: (i) preparing polyurethane A: under a nitrogen atmosphere, taking isophorone diisocyanate (diisocyanate), castor oil, an organic bismuth catalyst, and p-tert-butylcatechol (inhibitor), heating to 55-60°C and stirring for 5-6h to obtain an NCO-terminated prepolymer; The NCO-terminated prepolymer, conductive filler, terminal hydroxy fumaryl chloride-octanediol copolyester, isophorone diisocyanate, octadecylamine polyoxyethylene ether, organic bismuth catalyst, tert-butylcatechol, and ethyl acetate (solvent) were mixed evenly, heated to 55-60°C under nitrogen protection for reaction for 2-3 hours, 1,4-butanediol (chain extender) was added, reacted at 55-60°C for 2-3 hours, and the solvent was removed to obtain polyurethane A; (ii) Preparation of polyurethane B: Ethyl acetate, hydroxy-terminated fumaryl chloride-octanediol copolyester, 2-aminophenol-5-(N,N-dimethyl)sulfonamide, organic bismuth catalyst, 4-tert-butylcatechol, conductive filler, and isophorone diisocyanate were mixed uniformly, heated to 55-60° C. under nitrogen atmosphere and reacted for 2-3 h, 1,4-butanediol was added, reacted at 55-60° C. for 1-2 h, and the solvent was removed to obtain polyurethane B; S2: taking polyurethane A and polyurethane B, mixing them to obtain a polyurethane mixture; adding a cross-linking auxiliary composition, stirring to obtain an adhesive; S3: coating the adhesive on the substrate and curing it to obtain a viscosity-reducing layer; and pasting a release film on the surface of the viscosity-reducing layer to obtain a UV viscosity-reducing film.
[0006] Polyurethane A has a multi-branched structure, a large molecular weight, high viscosity, good mechanical strength, good antistatic properties, and small molecule additives are not easy to precipitate; after polyurethane B is blended with polyurethane A, on the one hand, its viscosity is reduced and processability is enhanced, and on the other hand, antistatic properties are improved.
[0007] Preferably, the specific steps of S3 are: applying the adhesive to the substrate, baking at 105° C. for 3 min to form a uniform 15 μm thick anti-viscosity layer, and then pasting a 50 μm PET release film on the surface of the anti-viscosity layer to obtain a UV anti-viscosity film.
[0008] Preferably, the NCO-terminated prepolymer comprises the following raw materials, in parts by mass: 10 to 15 parts of isophorone diisocyanate, 1.5 to 2.5 times the mass of isophorone diisocyanate of castor oil, 0.01 to 0.02% of the mass of isophorone diisocyanate of an organic bismuth catalyst, and 0.02 to 0.04% of the mass of isophorone diisocyanate of p-tert-butylcatechol; The polyurethane A comprises the following raw materials, calculated by weight: 3-4 parts of NCO-terminated prepolymer, 0.5-1.5 parts of conductive filler, 4-6 parts of terminal hydroxy fumaryl chloride-octanediol copolyester, 3-5 parts of isophorone diisocyanate, 1-2 parts of octadecylamine polyoxyethylene ether, 0.01-0.02% of the mass of isophorone diisocyanate by organic bismuth catalyst, 0.02-0.04% of the mass of isophorone diisocyanate by tert-butylcatechol, 20-30 parts of ethyl acetate, and 0.4-0.6 parts of 1,4-butanediol.
[0009] Preferably, the polyurethane B comprises the following raw materials, in parts by mass: 20 to 30 parts of ethyl acetate, 5 to 6 parts of terminal hydroxyfumaryl chloride-octanediol copolyester, 1 to 2 parts of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, 0.01 to 0.02% of the mass of isophorone diisocyanate in the amount of an organic bismuth catalyst, 0.02 to 0.04% of the mass of isophorone diisocyanate in the amount of p-tert-butylcatechol, 0.2 to 0.4 parts of a conductive filler, 3 to 4 parts of isophorone diisocyanate, and 0.2 to 0.3 parts of 1,4-butanediol.
[0010] Preferably, in the polyurethane mixture, the mass ratio of polyurethane A to polyurethane B is (1-2):1; in the adhesive, the amount of the cross-linking aid composition added is 3-5% of the mass of the polyurethane mixture.
[0011] Preferably, the cross-linking auxiliary composition comprises isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive in a mass ratio of (5-6):(1-2):(1-2); The preparation of the modified additive comprises the following steps: taking 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, isophorone diisocyanate, oleic acid, N-(3-hydroxyphenyl)acetamide, benzene, and acetone, stirring at 40-50° C. for 1-2 hours, removing benzene and acetone, and obtaining the modified additive; The preparation of the multifunctional active additive comprises the following steps: taking triallyl carbinol, toluene-2,4,6-triyl triisocyanate (triisocyanate), and benzene, stirring at 40-50° C. for 1-2 hours, and removing benzene to obtain the multifunctional active additive.
[0012] Isocyanate ethyl acrylate contains one double bond, and has a slow photocuring rate but strong dilution ability; multifunctional active additives contain three double bonds, and have weak dilution ability but fast photocuring rate; The modified additive is prepared by reacting oxygen-containing groups with isocyanate groups using 2-methyl-2-acrylate-2,3-dihydroxypropyl ester, isophorone diisocyanate, oleic acid, and N-(3-hydroxyphenyl)acetamide as raw materials. It can be used as a diluent and can participate in light curing. At the same time, because it contains chain segments similar to polyurethane A (oleic acid and castor oil) and polyurethane B (N-(3-hydroxyphenyl)acetamide and 2-aminophenol-5-(N,N-dimethyl)sulfonamide), it can improve the antistatic property and the compatibility of the two. The raw materials of the auxiliary cross-linking composition all contain isocyanate groups and have good compatibility with the polyurethane mixture, but the added amount should not be too much, otherwise it will lead to excessive cross-linking between polyurethane A and polyurethane B, increase viscosity, and reduce processability and mechanical properties.
[0013] Preferably, the modifying additive comprises the following raw materials, in parts by mass: 5 to 10 parts of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, 10 to 15 parts of isophorone diisocyanate, 1 to 2 parts of oleic acid, 0.5 to 1 part of N-(3-hydroxyphenyl)acetamide, 40 to 60 parts of benzene, and 40 to 60 parts of acetone; the multifunctional active additive comprises the following raw materials, in parts by mass: 10 to 15 parts of triallyl carbinol, 10 to 15 parts of toluene-2,4,6-triyl triisocyanate, and 80 to 100 parts of benzene.
[0014] Preferably, the cross-linking aid composition comprises isocyanate ethyl acrylate, a modifying additive and a multifunctional active additive in a mass ratio of (5-6):(1-2):(1-2); the preparation of the modifying additive comprises the following steps: taking 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, isophorone diisocyanate, oleic acid, N-(3-hydroxyphenyl)acetamide, benzene and acetone, stirring at 50°C for 1 hour, removing benzene and acetone to obtain the modifying additive; the preparation of the multifunctional active additive comprises the following steps: taking triallyl carbinol, toluene-2,4,6-triyl triisocyanate and benzene, stirring at 50°C for 1 hour, removing benzene, and obtaining a multifunctional active additive.
[0015] Preferably, the preparation of the terminal hydroxy fumaryl chloride-octanediol copolyester refers to the prior art; specifically comprising the following steps: taking fumaroyl chloride and tetrahydrofuran, mixing them evenly to obtain a fumaroyl chloride solution; taking 1,8-octanediol, triethylamine, tetrahydrofuran, and 4-tert-butylcatechol, mixing them evenly; keeping stirring, dropping the fumaroyl chloride solution, stirring, centrifuging to remove by-products, precipitating with water to obtain a crude product, washing, and drying overnight to obtain a terminal hydroxy fumaryl chloride-octanediol copolyester; The fumaryl chloride solution comprises the following raw materials, calculated by weight: 10-15 parts of fumaryl chloride and 40-60 parts of tetrahydrofuran; the terminal hydroxy fumaryl chloride-octanediol copolyester comprises the following raw materials, calculated by weight: 15-20 parts of 1,8-octanediol, 15-20 parts of triethylamine, 50-80 parts of tetrahydrofuran, and 0.03-0.05 parts of 4-tert-butylcatechol.
[0016] The terminal hydroxy fumaryl chloride-octanediol copolyester contains double bonds, which can participate in the UV viscosity reduction in the subsequent step.
[0017] Preferably, the preparation of the conductive filler comprises the following steps: graphite, ethanol, water, isocyanate silane coupling agent and vinyl silane coupling agent are mixed evenly, and stirred at 50° C. for 5 hours to obtain a conductive filler; wherein the mass ratio of graphite, isocyanate silane coupling agent and vinyl silane coupling agent is 15:1:1.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: polyurethane A, polyurethane B and a cross-linking auxiliary composition are used to prepare an adhesive, and a UV viscosity-reducing film is prepared using the adhesive; polyurethane A is a multi-branched structure based on castor oil, has a large molecular weight, and has the advantages of good mechanical strength, good toughness and high viscosity, and castor oil plays a lubricating role, which can reduce static electricity generated by friction; the conductive filler is graphite modified by an isocyanate silane coupling agent and a vinyl silane coupling agent, has good antistatic properties and can be uniformly dispersed in polyurethane, and its double bonds can also participate in the UV viscosity-reducing reaction to accelerate the viscosity-reducing process; since the addition of filler will reduce the contact area between the adhesive layer and the substrate, resulting in a decrease in peel strength, it is not advisable to add too much filler, therefore, the addition of octadecylamine polyoxyethylene ether, on the one hand, plays an antistatic role itself, on the other hand, improves the hydrophilicity of castor oil, and further enhances the antistatic ability; octadecylamine polyoxyethylene ether is introduced into polyurethane A through reaction, which improves the problem of its outward precipitation leading to a decrease in viscosity; The polyurethane B is introduced. The molecular weight of the polyurethane B is relatively low. After being blended with the polyurethane A, its processing performance can be improved. The polyurethane B is added with 2-aminophenol-5-(N,N-dimethyl)sulfonamide, which has good compatibility with the polyurethane matrix and contains hydrophilic groups, which helps to improve the antistatic property. The auxiliary cross-linking composition includes a certain proportion of isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive; all of them are polymerizable monomers containing a C=C double bond, which can reduce the viscosity of the glue and facilitate processing, and can also participate in subsequent light curing; isocyanate ethyl acrylate contains one double bond, and the light curing rate is slow but the dilution ability is strong; the multifunctional active additive contains three double bonds, and the dilution ability is weak but the light curing rate is fast; the modifying additive contains oleic acid and N-(3-hydroxyphenyl)acetamide, which can be used as a diluent and can participate in light curing, and because it contains chain segments similar to those of polyurethane A and polyurethane B, it can also improve the compatibility of the two and further improve the performance; the raw materials of the auxiliary cross-linking composition also contain isocyanate groups, and have good compatibility with the polyurethane mixture, but the added amount should not be too much, otherwise it will cause excessive cross-linking between polyurethane A and polyurethane B, increase viscosity, and reduce processability and mechanical properties. DETAILED DESCRIPTION
[0019] In the following specific embodiments, the parts are by mass unless otherwise specified; at the same time, the following is a preferred embodiment of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principles of the embodiments of the present invention are within the scope of protection of the present invention.
[0020] The preparation of terminal hydroxy fumaryl chloride-octanediol copolyester comprises the following steps: taking 15 parts of fumaryl chloride and 50 parts of tetrahydrofuran, mixing them evenly to obtain a fumaryl chloride solution; taking 15 parts of 1,8-octanediol, 20 parts of triethylamine, 80 parts of tetrahydrofuran and 0.05 parts of 4-tert-butylcatechol, mixing them evenly; keeping stirring, dropping the fumaryl chloride solution, the dropping time is 1 hour, the dropping temperature is 5°C, and after the dropping is completed, the temperature is raised to 30°C and stirred for 3 hours; centrifuging to remove by-products, precipitating with water to obtain a crude product, washing, and drying overnight to obtain a terminal hydroxy fumaryl chloride-octanediol copolyester.
[0021] The modified additive includes the following raw materials, calculated by mass: 8 parts of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, 12 parts of isophorone diisocyanate, 1 part of oleic acid, 0.5 parts of N-(3-hydroxyphenyl)acetamide, 60 parts of benzene, and 60 parts of acetone.
[0022] The multifunctional active additive comprises the following raw materials, calculated by weight: 12 parts of triallyl carbinol, 10 parts of toluene-2,4,6-triyl triisocyanate, and 100 parts of benzene.
[0023] Example 1: S1: Under nitrogen atmosphere, 12 parts of isophorone diisocyanate, 1.8 times the mass of castor oil of isophorone diisocyanate, 0.015% of the mass of organic bismuth catalyst of isophorone diisocyanate, and 0.03% of the mass of tert-butyl catechol of isophorone diisocyanate were taken, and the temperature was raised to 60°C and stirred for 6 hours to obtain an NCO-terminated prepolymer; 4 parts of NCO-terminated prepolymer, 1 part of conductive filler, and 5 parts of terminal hydroxyl-rich Maleyl chloride-octanediol copolyester, 4 parts of isophorone diisocyanate, 1.5 parts of octadecylamine polyoxyethylene ether, 0.02% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.02% of the mass of isophorone diisocyanate p-tert-butylcatechol, 25 parts of ethyl acetate, under nitrogen protection, heated to 60°C for reaction for 3h, added 0.5 parts of 1,4-butanediol, reacted at 60°C for 3h, removed the solvent, and obtained polyurethane A; S2: Take 25 parts of ethyl acetate, 6 parts of terminal hydroxyfumaryl chloride-octanediol copolyester, 1.5 parts of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, 0.015% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.03% of the mass of isophorone diisocyanate p-tert-butylcatechol, 0.3 parts of conductive filler, 3 parts of isophorone diisocyanate, heat to 60°C under nitrogen atmosphere, react for 2h, add 0.2 parts of 1,4-butanediol, react at 60°C for 1h, remove the solvent, and obtain polyurethane B; S3: taking polyurethane A and polyurethane B in a mass ratio of 1.5:1, mixing to obtain a polyurethane mixture, adding a cross-linking auxiliary composition (including isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive in a mass ratio of 5:1:1) in an amount of 4% by mass of the polyurethane mixture, stirring for 1 hour to obtain an adhesive; S4: The adhesive is coated on the substrate and baked at 105° C. for 3 min to form a uniform 15 μm thick anti-viscosity layer, and then a 50 μm PET release film is attached to the surface of the anti-viscosity layer to obtain a UV anti-viscosity film.
[0024] Example 2: S1: Under nitrogen atmosphere, 10 parts of isophorone diisocyanate, 1.5 times the mass of castor oil of isophorone diisocyanate, 0.015% of the mass of organic bismuth catalyst of isophorone diisocyanate, and 0.03% of the mass of tert-butyl catechol of isophorone diisocyanate were taken, and the temperature was raised to 60°C and stirred for 6 hours to obtain an NCO-terminated prepolymer; 3 parts of NCO-terminated prepolymer, 0.5 parts of conductive filler, and 4 parts of terminal hydroxyl radical were taken. 1,4-Butanediol-1,2-diol copolyester, 3 parts of isophorone diisocyanate, 1 part of octadecylamine polyoxyethylene ether, 0.02% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.02% of the mass of isophorone diisocyanate p-tert-butylcatechol, 25 parts of ethyl acetate, under nitrogen protection, heated to 60°C for reaction for 3h, added 0.5 parts of 1,4-butanediol, reacted at 60°C for 3h, removed the solvent, and obtained polyurethane A; S2: Take 25 parts of ethyl acetate, 5 parts of terminal hydroxyfumaryl chloride-octanediol copolyester, 1 part of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, 0.015% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.03% of the mass of isophorone diisocyanate p-tert-butylcatechol, 0.2 parts of conductive filler, 3 parts of isophorone diisocyanate, heat to 60°C under nitrogen atmosphere, react for 2h, add 0.2 parts of 1,4-butanediol, react at 60°C for 1h, remove the solvent, and obtain polyurethane B; S3: taking polyurethane A and polyurethane B in a mass ratio of 2:1, mixing to obtain a polyurethane mixture, adding a cross-linking auxiliary composition (including isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive in a mass ratio of 6:2:1) in an amount of 3% by mass of the polyurethane mixture, and stirring for 1 hour to obtain an adhesive; S4: The adhesive is coated on the substrate and baked at 105° C. for 3 min to form a uniform 15 μm thick anti-viscosity layer, and then a 50 μm PET release film is attached to the surface of the anti-viscosity layer to obtain a UV anti-viscosity film.
[0025] Example 3: S1: Under nitrogen atmosphere, 15 parts of isophorone diisocyanate, 2.5 times the mass of castor oil of isophorone diisocyanate, 0.015% of the mass of organic bismuth catalyst of isophorone diisocyanate, and 0.03% of the mass of tert-butyl catechol of isophorone diisocyanate were taken, and the temperature was raised to 60°C and stirred for 6 hours to obtain an NCO-terminated prepolymer; 4 parts of NCO-terminated prepolymer, 1.5 parts of conductive filler, and 6 parts of terminal hydroxyl radical were taken. 1,4-Butanediol-1,2- ... S2: Take 25 parts of ethyl acetate, 6 parts of terminal hydroxyfumaryl chloride-octanediol copolyester, 2 parts of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, 0.015% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.03% of the mass of isophorone diisocyanate p-tert-butylcatechol, 0.4 parts of conductive filler, 4 parts of isophorone diisocyanate, heat to 60°C under nitrogen atmosphere, react for 2h, add 0.2 parts of 1,4-butanediol, react at 60°C for 1h, remove the solvent, and obtain polyurethane B; S3: taking polyurethane A and polyurethane B in a mass ratio of 1:1, mixing to obtain a polyurethane mixture, adding a cross-linking auxiliary composition (including isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive in a mass ratio of 6:1:2) in an amount of 5% by mass of the polyurethane mixture, and stirring for 1 hour to obtain an adhesive; S4: The adhesive is coated on the substrate and baked at 105° C. for 3 min to form a uniform 15 μm thick anti-viscosity layer, and then a 50 μm PET release film is attached to the surface of the anti-viscosity layer to obtain a UV anti-viscosity film.
[0026] Comparative Example 1 (the addition amounts of polyurethane A and polyurethane B were changed, and the remaining steps were consistent with those of Example 1): S1: Under a nitrogen atmosphere, 12 parts of isophorone diisocyanate, 1.8 times the mass of castor oil of isophorone diisocyanate, 0.015% of the mass of isophorone diisocyanate of an organic bismuth catalyst, and 0.03% of the mass of isophorone diisocyanate of p-tert-butylcatechol were taken, the temperature was raised to 60° C. and stirred for 6 hours to obtain an NCO-terminated prepolymer; 4 parts of the NCO-terminated prepolymer were taken; Polymer, 1 part of conductive filler, 5 parts of terminal hydroxy fumaryl chloride-octanediol copolyester, 4 parts of isophorone diisocyanate, 1.5 parts of octadecylamine polyoxyethylene ether, 0.02% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.02% of the mass of isophorone diisocyanate p-tert-butylcatechol, 25 parts of ethyl acetate, under nitrogen protection, heated to 60°C for reaction for 3h, added 0.5 parts of 1,4-butanediol, reacted at 60°C for 3h, removed the solvent to obtain polyurethane A; S2: Take 25 parts of ethyl acetate, 6 parts of terminal hydroxyfumaryl chloride-octanediol copolyester, 1.5 parts of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, 0.015% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.03% of the mass of isophorone diisocyanate p-tert-butylcatechol, 0.3 parts of conductive filler, 3 parts of isophorone diisocyanate, heat to 60°C under nitrogen atmosphere, react for 2h, add 0.2 parts of 1,4-butanediol, react at 60°C for 1h, remove the solvent, and obtain polyurethane B; S3: taking polyurethane A and polyurethane B in a mass ratio of 1:2, mixing to obtain a polyurethane mixture, adding a cross-linking auxiliary composition (including isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive in a mass ratio of 5:1:1) in an amount of 4% by mass of the polyurethane mixture, stirring for 1 hour to obtain an adhesive; S4: The adhesive is coated on the substrate and baked at 105° C. for 3 min to form a uniform 15 μm thick anti-viscosity layer, and then a 50 μm PET release film is attached to the surface of the anti-viscosity layer to obtain a UV anti-viscosity film.
[0027] Comparative Example 2 (the preparation method of polyurethane A and B is changed, and the remaining steps are consistent with Example 1): S1: Under a nitrogen atmosphere, 12 parts of isophorone diisocyanate, 1.8 times the mass of castor oil of isophorone diisocyanate, 0.015% of the mass of isophorone diisocyanate of an organic bismuth catalyst, and 0.03% of the mass of isophorone diisocyanate of tert-butyl catechol were taken, and the temperature was raised to 60° C. and stirred for 6 hours to obtain an NCO-terminated prepolymer; 4 parts of the NCO-terminated prepolymer, 2.5 parts of Conductive filler, 6.5 parts of terminal hydroxy fumaryl chloride-octanediol copolyester, 4 parts of isophorone diisocyanate, 0.02% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.02% of the mass of isophorone diisocyanate p-tert-butylcatechol, 25 parts of ethyl acetate, under nitrogen protection, heated to 60°C for reaction for 3h, added 0.5 parts of 1,4-butanediol, reacted at 60°C for 3h, added 1.5 parts of octadecylamine polyoxyethylene ether, stirred evenly, and removed the solvent to obtain polyurethane A; S2: Under nitrogen atmosphere, take 25 parts of ethyl acetate, 8 parts of terminal hydroxyfumaryl chloride-octanediol copolyester, 0.015% of isophorone diisocyanate by weight of organic bismuth catalyst, 0.03% of isophorone diisocyanate by weight of tert-butylcatechol, 0.3 parts of conductive filler, 3 parts of isophorone diisocyanate, heat to 60°C and react for 2h, add 0.2 parts of 1,4-butanediol, react at 60°C for 1h, add 1.5 parts of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, stir evenly, remove the solvent, and obtain polyurethane B; S3: taking polyurethane A and polyurethane B in a mass ratio of 1.5:1, mixing to obtain a polyurethane mixture, adding a cross-linking auxiliary composition (including isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive in a mass ratio of 5:1:1) in an amount of 4% by mass of the polyurethane mixture, stirring for 1 hour to obtain an adhesive; S4: The adhesive is coated on the substrate and baked at 105° C. for 3 min to form a uniform 15 μm thick anti-viscosity layer, and then a 50 μm PET release film is attached to the surface of the anti-viscosity layer to obtain a UV anti-viscosity film.
[0028] Comparative Example 3 (changing the amount of the auxiliary cross-linking composition added, the remaining method steps are consistent with Example 1): S1: Under a nitrogen atmosphere, take 12 parts of isophorone diisocyanate, 1.8 times the mass of castor oil of isophorone diisocyanate, 0.015% of the mass of isophorone diisocyanate of an organic bismuth catalyst, and 0.03% of the mass of isophorone diisocyanate of tert-butyl catechol, heat to 60 ° C and stir for 6 hours to obtain an NCO-terminated prepolymer; take 4 parts of the NCO-terminated prepolymer , 1 part of conductive filler, 5 parts of terminal hydroxy fumaryl chloride-octanediol copolyester, 4 parts of isophorone diisocyanate, 1.5 parts of octadecylamine polyoxyethylene ether, 0.02% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.02% of the mass of isophorone diisocyanate p-tert-butylcatechol, 25 parts of ethyl acetate, under nitrogen protection, heated to 60°C for reaction for 3h, added 0.5 parts of 1,4-butanediol, reacted at 60°C for 3h, removed the solvent to obtain polyurethane A; S2: Take 25 parts of ethyl acetate, 6 parts of terminal hydroxyfumaryl chloride-octanediol copolyester, 1.5 parts of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, 0.015% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.03% of the mass of isophorone diisocyanate p-tert-butylcatechol, 0.3 parts of conductive filler, 3 parts of isophorone diisocyanate, heat to 60°C under nitrogen atmosphere, react for 2h, add 0.2 parts of 1,4-butanediol, react at 60°C for 1h, remove the solvent, and obtain polyurethane B; S3: taking polyurethane A and polyurethane B in a mass ratio of 1.5:1, mixing to obtain a polyurethane mixture, adding a cross-linking auxiliary composition (including isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive in a mass ratio of 5:1:1) in an amount of 6% by mass of the polyurethane mixture, stirring for 1 hour to obtain an adhesive; S4: The adhesive is coated on the substrate and baked at 105° C. for 3 min to form a uniform 15 μm thick anti-viscosity layer, and then a 50 μm PET release film is attached to the surface of the anti-viscosity layer to obtain a UV anti-viscosity film.
[0029] Comparative Example 4 (the raw materials of the cross-linking aid composition are changed, and the other method steps are consistent with Example 1): S1: Under a nitrogen atmosphere, 12 parts of isophorone diisocyanate, 1.8 times the mass of castor oil of isophorone diisocyanate, 0.015% of the mass of isophorone diisocyanate of an organic bismuth catalyst, and 0.03% of the mass of isophorone diisocyanate of tert-butyl catechol were taken, and the temperature was raised to 60° C. and stirred for 6 hours to obtain an NCO-terminated prepolymer; 4 parts of the NCO-terminated prepolymer were taken , 1 part of conductive filler, 5 parts of terminal hydroxy fumaryl chloride-octanediol copolyester, 4 parts of isophorone diisocyanate, 1.5 parts of octadecylamine polyoxyethylene ether, 0.02% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.02% of the mass of isophorone diisocyanate p-tert-butylcatechol, 25 parts of ethyl acetate, under nitrogen protection, heated to 60°C for reaction for 3h, added 0.5 parts of 1,4-butanediol, reacted at 60°C for 3h, removed the solvent to obtain polyurethane A; S2: Take 25 parts of ethyl acetate, 6 parts of terminal hydroxyfumaryl chloride-octanediol copolyester, 1.5 parts of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, 0.015% of the mass of isophorone diisocyanate organic bismuth catalyst, 0.03% of the mass of isophorone diisocyanate p-tert-butylcatechol, 0.3 parts of conductive filler, 3 parts of isophorone diisocyanate, heat to 60°C under nitrogen atmosphere, react for 2h, add 0.2 parts of 1,4-butanediol, react at 60°C for 1h, remove the solvent, and obtain polyurethane B; S3: taking polyurethane A and polyurethane B in a mass ratio of 1.5:1, mixing to obtain a polyurethane mixture, adding a cross-linking auxiliary composition (including isocyanate ethyl acrylate and multifunctional active additives in a mass ratio of 6:1) in an amount of 4% by mass of the polyurethane mixture, stirring for 1 hour to obtain an adhesive; S4: The adhesive is coated on the substrate and baked at 105° C. for 3 min to form a uniform 15 μm thick anti-viscosity layer, and then a 50 μm PET release film is attached to the surface of the anti-viscosity layer to obtain a UV anti-viscosity film.
[0030] In the above examples, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethyl isocyanate acrylate (CAS: 13641-96-8); 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester (A919744, Hubei Wande Chemical Co., Ltd.); oleic acid (S30008, Shanghai Yuanye); N-(3-hydroxyphenyl)acetamide (CAS: 621-42-1); isophorone diisocyanate (CAS: 4098-71-9); ethanol (CAS: 64-17-5); triallyl carbinol (CAS: 10202-75-2); toluene-2,4,6-triyl triisocyanate (CAS: 7373-26-4); benzene (CAS: 71-43-2); fumaryl chloride (CAS: 627-63-4); tetrahydrofuran (CAS: 109-99-9); 1 ,8-octanediol (CAS: 629-41-4); triethylamine (CAS: 121-44-8); 4-tert-butylcatechol / 4-tert-butylcatechol (CAS: 98-29-3); castor oil (S24344, Shanghai Yuanye); organic bismuth catalyst (JD200326093411, Shanghai Jiader Chemical Technology Co., Ltd.); octadecylamine polyoxyethylene ether (CAS: 26635-92-7); ethyl acetate (CAS: 14 1-78-6); 1,4-butanediol (CAS: 110-63-4); 2-aminophenol-5-(N,N-dimethyl)sulfonamide (WD10182, Hubei Wonder Chemical Co., Ltd.); graphite (JK-R0810, Jingkang Biological); isocyanate silane coupling agent (isocyanate propyl triethoxysilane, CAS: 24801-88-5); vinyl silane coupling agent (vinyl triethoxysilane, CAS: 78-08-0).
[0031] Experiment: The adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were (1) tested for their 180° peel strength (gf / 25mm) before and after UV treatment according to GB-2792-81; (2) coated the adhesive on a substrate, baked at 105°C for 3 min, and tested for their surface resistance (Ω) according to GB / T2439-2001; (3) tested for tensile strength (MPa) using a micro-controlled electronic universal testing machine according to GB / T 2567-2021, with a tensile rate of 2 mm / min; see the table below for specific data;
[0032] Conclusion: In comparative example 1, the addition amount of polyurethane A and polyurethane B is changed. The addition amount of polyurethane B is too large, resulting in reduced performance, which shows the importance of ratio; in comparative example 2, the preparation method of polyurethane A and polyurethane B is changed, the conductive filler is increased, octadecylamine polyoxyethylene ether and 2-aminophenol-5-(N,N-dimethyl)sulfonamide are added by direct mixing. Due to compatibility and other problems, the performance is reduced; in comparative example 3, the addition amount of the auxiliary cross-linking composition is increased, and the tensile strength is reduced due to excessive cross-linking; in comparative example 4, the raw materials of the auxiliary cross-linking composition are changed, ethyl isocyanate acrylate is added, and there is no modified additive, and the performance is not as good as the embodiment; in summary, the UV anti-viscosity film prepared by the adhesive prepared by the present invention has good tensile strength and antistatic properties, and at the same time ensures that it has excellent adhesion before UV irradiation, which is greater than 2000 gf / inch, and the adhesion decreases after irradiation and is easy to peel off, which is less than 5 gf / inch.
[0033] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing an antistatic UV anti-viscosity film, characterized in that: The following steps are involved: S1: (i) Preparation of polyurethane A: Under nitrogen atmosphere, diisocyanate, castor oil, organic bismuth catalyst and polymerization inhibitor were mixed, heated to 55-60°C and stirred for 5-6h to obtain NCO-terminated prepolymer; Take NCO-terminated prepolymer, conductive filler, terminal hydroxy fumaryl chloride-octanediol copolyester, diisocyanate, octadecylamine polyoxyethylene ether, organic bismuth catalyst, and inhibitor and add them to the solvent in sequence; heat to 55-60°C under nitrogen protection and react for 2-3 hours, add chain extender, react at 55-60°C for 2-3 hours, remove solvent, and obtain polyurethane A; (ii) Preparation of polyurethane B: add terminal hydroxy fumaryl chloride-octanediol copolyester, 2-aminophenol-5-(N,N-dimethyl)sulfonamide, organic bismuth catalyst, polymerization inhibitor, conductive filler and diisocyanate to a solvent in sequence; heat to 55-60°C under nitrogen protection and react for 2-3 hours, add a chain extender, react at 55-60°C for 1-2 hours, remove the solvent, and obtain polyurethane B; S2: taking polyurethane A and polyurethane B, mixing them to obtain a polyurethane mixture; adding a cross-linking auxiliary composition, stirring evenly to obtain an adhesive; S3: coating the adhesive on the substrate and curing it to obtain a viscosity-reducing layer; and pasting a release film on the surface of the viscosity-reducing layer to obtain a UV viscosity-reducing film.
2. The method for preparing an antistatic UV anti-viscosity film according to claim 1, characterized in that: In the polyurethane mixture, the mass ratio of polyurethane A to polyurethane B is (1-2):1; in the adhesive, the amount of the cross-linking aid composition added is 3-5wt% of the polyurethane mixture.
3. The method for preparing an antistatic UV anti-viscosity film according to claim 2, characterized in that: The cross-linking aid composition comprises isocyanate ethyl acrylate, a modifying additive, and a multifunctional active additive in a mass ratio of (5-6):(1-2):(1-2).
4. The method for preparing an antistatic UV viscosity-reducing film according to claim 3, characterized in that: The preparation of the modified additive comprises the following steps: taking 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, diisocyanate, oleic acid, N-(3-hydroxyphenyl)acetamide, benzene, and acetone, stirring at 40-50° C. for 1-2 hours, removing benzene and acetone, and obtaining the modified additive; The preparation of the multifunctional active additive comprises the following steps: taking triallyl carbinol, triisocyanate and benzene, stirring at 40-50° C. for 1-2 hours, and removing benzene to obtain the multifunctional active additive.
5. The method for preparing an antistatic UV anti-viscosity film according to claim 4, characterized in that: The modified additive comprises the following raw materials, calculated by mass: 5 to 10 parts of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, 10 to 15 parts of diisocyanate, 1 to 2 parts of oleic acid, 0.5 to 1 part of N-(3-hydroxyphenyl)acetamide, 40 to 60 parts of benzene, and 40 to 60 parts of acetone; The multifunctional active additive comprises the following raw materials, calculated by weight: 10-15 parts of triallyl carbinol, 10-15 parts of triisocyanate, and 80-100 parts of benzene.
6. The method for preparing an antistatic UV anti-viscosity film according to claim 1, characterized in that: The preparation of the conductive filler comprises the following steps: Graphite, ethanol, water, isocyanate silane coupling agent and vinyl silane coupling agent are mixed evenly, and stirred at 45-55° C. for 4-6 hours to obtain a conductive filler; wherein the mass ratio of graphite, isocyanate silane coupling agent and vinyl silane coupling agent is (10-15):1:
1.
7. The method for preparing an antistatic UV anti-viscosity film according to claim 1, characterized in that: In the raw materials of the NCO-terminated prepolymer, the mass of castor oil accounts for 1.5 to 2.5 times the mass of diisocyanate; The polyurethane A comprises the following raw materials, calculated by weight: 3-4 parts of NCO-terminated prepolymer, 0.5-1.5 parts of conductive filler, 4-6 parts of terminal hydroxy fumaryl chloride-octanediol copolyester, 3-5 parts of diisocyanate, 1-2 parts of octadecylamine polyoxyethylene ether, 20-30 parts of solvent, and 0.4-0.6 parts of chain extender.
8. The method for preparing an antistatic UV anti-viscosity film according to claim 1, characterized in that: The polyurethane B comprises the following raw materials, calculated by mass: 20-30 parts of solvent, 5-6 parts of terminal hydroxy fumaryl chloride-octanediol copolyester, 1-2 parts of 2-aminophenol-5-(N,N-dimethyl)sulfonamide, 0.2-0.4 parts of conductive filler, 3-4 parts of diisocyanate, and 0.2-0.3 parts of chain extender.
9. The UV anti-viscosity film obtained according to the method for preparing an antistatic UV anti-viscosity film according to any one of claims 1 to 8.
Citation Information
Patent Citations
Synthetic method of 2-aminophenol-4-sulfonamide
CN104592064A
Preparation method of castor oil-based fully-crosslinked UV (Ultraviolet) photoinduced peelable glue for silicon wafer cutting process
CN112646537A
UV viscosity-reducing adhesive and preparation method thereof
CN113698908A
UV viscosity-reducing adhesive with antistatic effect and preparation method of viscosity-reducing adhesive
CN113861928A
Plasticizer-resistant viscosity-reducing polymer composition and UV viscosity-reducing adhesive tape
CN116875237A
